Developing Bilingual (Indonesian - English) Descriptions for Museum Angkut’s Vehicle Collections - Agil Miftakul Putra (Jurnal Linguistik Terapan, 2020)
This project is a research and development research. The purposes of the research are (1) to create bilingual collection descriptions and (2) to help Museum Angkut visitor easier to get information. In conducting this study, the writer did analysis, design, development, implementation, and evaluation. The result of the study covered two main points. First is the collection descriptions in Indonesian and English. Second, the descriptions were validated by a translation expert, and it was evaluated by 32 respondents. The bilingual collection descriptions were already revised based on the translation experts' feedback and the respondents' suggestion. The final product of this research is especially beneficial for Museum Angkut and future researcher developing the same text. Museum Angkut can develop and improve the idea in this research. Moreover, English Department Student of State Polytechnic of Malang may find similar solution for similar problem of their research.